Android-based Didactical Design for Learning Lines and Angles: An Interpretive Didactical Design Research - Muhibban, Muhibban; Isnawan, Muhamad Galang; Aziz, Abdul (Nashir Al-Kutub Indonesia, 2023)
Lines and angles are quite important mathematical concepts. This is proven because lines and angles cannot be separated in life. However, lines and angles actually become a problem/obstacle in the classroom. The purpose of this research is to determine the description of students' learning obstacles in the material on lines and angles for class VIII MTs NW Pringgajurang, then a didactic design for learning lines and angles will be prepared. The research design used is didactical design research-interpretive. The participants in this research were Class VIII students at MTs NW Pringgajurang with an age range of 12 to 14 years. The researcher is the main instrument in this research, with several additional instruments such as tests for understanding lines and angles, student biodata, interview guides and didactic designs for lines and angles. The data analysis technique used in this research is thematic data analysis. This thematic analysis is used as a basic foundation for the analytical process in qualitative research, by paying attention to the results of the data collection carried out. The results of the research show that students experience learning obstacles with ontogenic psychological and ontogenic conceptual types. With this Android-based didactic design, it is hoped that it will be able to minimize barriers to students' learning on line and angle material at MTs NW Pringgajurang.